1998
DOI: 10.2172/1234
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide Incorporation in Secondary Crystalline Minerals Resulting from Chemical Weathering of Selected Waste Glasses: Progress Report for Subtask 3d

Abstract: SummaryExperiments were conducted in fiscal year 1998 by Pacific Northwest National Laboratory' to evaluate potential incorporation of radionuclides in secondary mineral phases that form from weathering vitrified nuclear waste glasses. These experiments were conducted as part of the Immobilized LowActivity Waste-Performance Assessment (ILAW-PA) to generate data on radionuclide mobilization and transport in a near-field environment of disposed vitrified wastes.An initial experiment was conducted to identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The degree of sequestration of 99 Tc in experiments using 1M NaOH solutions could not be assessed due to matrix interference during scintillation counting. The degree of radionuclide sequestration observed for these waste glasses was comparable to the previous data obtained for other weathered glasses (LD6 and LAWA33) containing zeolitic minerals as the crystalline weathering products (Mattigod et al 1998(Mattigod et al , 2002a. These data indicate that one of the critical factors in radionuclide sequestration is the types and quantities of secondary minerals that form from weathering glasses.…”
Section: Radionuclide Sequestration Experimentssupporting
confidence: 84%
See 2 more Smart Citations
“…The degree of sequestration of 99 Tc in experiments using 1M NaOH solutions could not be assessed due to matrix interference during scintillation counting. The degree of radionuclide sequestration observed for these waste glasses was comparable to the previous data obtained for other weathered glasses (LD6 and LAWA33) containing zeolitic minerals as the crystalline weathering products (Mattigod et al 1998(Mattigod et al , 2002a. These data indicate that one of the critical factors in radionuclide sequestration is the types and quantities of secondary minerals that form from weathering glasses.…”
Section: Radionuclide Sequestration Experimentssupporting
confidence: 84%
“…Our previous studies with SRL202, LD6, and LAWA33 glasses showed that the weathered glasses exhibited different degrees of sequestration of radionuclides that were spiked into contacting solutions (Mattigod et al 1998(Mattigod et al , 2002a. These studies also showed that the secondary crystalline minerals that formed from weathering glasses sequestered portions of the radionuclides.…”
Section: Radionuclide Sequestration and Mobilization Experimentsmentioning
confidence: 94%
See 1 more Smart Citation
“…and U Mobilitv. Past l l A W studies have shown that zeolites form as secondary phases following the glass waste form dissolution (Mann et al 1996 andMattigod et al 1998). Zeolites have the ability to sequester many different ions within their crystalline structure.…”
Section: -05mentioning
confidence: 99%
“…Zeolites have the ability to sequester many different ions within their crystalline structure. Preliminary tests (Mattigod et al 1998) have shown that these four potentially mobile contaminants are partially incorporated into the structures of the weathering products of 5-86 RPP-6702, Rev. 0 Formerly HNF-SD-WM-PAP-062 Rev.…”
Section: -05mentioning
confidence: 99%